EXPOSIÇÃO CONHECER PARA PRESERVAR: FAUNA E FLORA REGIONAIS - Correa, Geodeli A. P.; Lima, Jonas D. N. d.; Klein, Fátima R. S.; Coelho, Geraldo C.; Ferreira, Francesca W.; Tissot-Squalli, Mara L.; Hames, Clarines (Salão do Conhecimento, 2013)
Resumo